New technology and rural development : the social impact - Campbell, M.J. (ed.) (London, 1990)
In most developing countries agriculture is still the predominant occupation of the majority of the people. Recently, however, the transfer of technology from developed to less developed countries has stimulated quite rapid change. This book contains a compara tive study of the impact of increased modernization in the rural sector in six important developing countries. It considers cases where the deliberate introduction of technology has formed part of a wider national development plan, and examples where technology has been introduced into communities as a result of pressure from within these communities. In both cases the impact of the tech nology can be seen to have been profound with new skills having to be learnt and new working relationships adopted.
Keywords: Rural development Developing countries